2003
DOI: 10.1086/379122
|View full text |Cite
|
Sign up to set email alerts
|

Probing Dark Energy with Baryonic Acoustic Oscillations from Future Large Galaxy Redshift Surveys

Abstract: We show that the measurement of the baryonic acoustic oscillations in large high redshift galaxy surveys offers a precision route to the measurement of dark energy. The cosmic microwave background provides the scale of the oscillations as a standard ruler that can be measured in the clustering of galaxies, thereby yielding the Hubble parameter and angular diameter distance as a function of redshift. This, in turn, enables one to probe dark energy. We use a Fisher matrix formalism to study the statistical error… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
1,122
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 771 publications
(1,142 citation statements)
references
References 98 publications
(109 reference statements)
15
1,122
0
5
Order By: Relevance
“…In 2003, several papers appeared discussing the acoustic scale as a standard ruler for the measurement of dark energy in higher redshift galaxy surveys (Eisenstein, 2002;Blake and Glazebrook, 2003;Hu and Haiman, 2003;Linder, 2003;Seo and Eisenstein, 2003). Compelling detections in 2005 intensified these plans (Cole et al, 2005;Eisenstein et al, 2005), with several observational surveys proposed and numerous theoretical investigations.…”
Section: The Current State Of Playmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2003, several papers appeared discussing the acoustic scale as a standard ruler for the measurement of dark energy in higher redshift galaxy surveys (Eisenstein, 2002;Blake and Glazebrook, 2003;Hu and Haiman, 2003;Linder, 2003;Seo and Eisenstein, 2003). Compelling detections in 2005 intensified these plans (Cole et al, 2005;Eisenstein et al, 2005), with several observational surveys proposed and numerous theoretical investigations.…”
Section: The Current State Of Playmentioning
confidence: 99%
“…However, any realistic bias relation must be at least somewhat non-linear, which alters the relative weighting of overdense and underdense regions and should shift the acoustic scale at second order. Early work attempted to measure this shift in simulations (Seo and Eisenstein, 2003;Angulo et al, 2008), but the volume of the simulations was insufficient to get a conclusive detection of the effect. More recently, explored galaxy bias as the ratio of the second-order to first-order bias term, finding shifts of a few tenths of a percent for reasonable bias cases.…”
Section: Non-linear Evolution and Galaxy Clustering Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of the baryon acoustic scale in the distribution of galaxies have established themselves as one of the most powerful tools for precision cosmology (Eisenstein, Hu & Tegmark 1998;Percival et al 2001;Blake & Glazebrook 2003;Hu & Haiman 2003;Seo & Eisenstein 2003;Linder 2003;Eisenstein et al 2005;Cole et al 2005;Beutler et al 2011;Blake et al 2011;Alam et al 2016). With the most recent measurements of the BAO scale in the BOSS survey we have now reached 1% precision in two redshift bins (Alam et al 2016;Beutler et al 2016a;Ross et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Considering impacts of early dark energy to the matter power spectrum, we estimated possible changes to the Baryon Acoustic Peak measurement of Eisenstein et al We found that these changes are roughly a factor of two smaller than the experimental errors on the A-parameter measured by Eisenstein et al Put another way, allowing for an dark energy contribution at last scattering slightly increases the systematic uncertainty in A. Whilst current BAO measurements are a useful probe for cosmological parameters of the late universe [16,17], they turn out to be less stringent for the early universe.…”
Section: Discussionmentioning
confidence: 90%